Comparison of the Screening Tests for Gestational Diabetes Mellitus between "One-Step" and "Two-Step" Methods among Thai Pregnant Women. (8th February 2018) - Luewan, Suchaya; Bootchaingam, Phenphan; Tongsong, Theera
Abstract : Objective . To compare the prevalence and pregnancy outcomes of GDM between those screened by the "one-step" (75 gm GTT) and "two-step" (100 gm GTT) methods. Methods . A prospective study was conducted on singleton pregnancies at low or average risk of GDM. All were screened between 24 and 28 weeks, using the one-step or two-step method based on patients' preference. The primary outcome was prevalence of GDM, and secondary outcomes included birthweight, gestational age, rates of preterm birth, small/large-for-gestational age, low Apgar scores, cesarean section, and pregnancy-induced hypertension. Results . A total of 648 women were screened: 278 in the one-step group and 370 in the two-step group. The prevalence of GDM was significantly higher in the one-step group; 32.0% versus 10.3%. Baseline characteristics and pregnancy outcomes in both groups were comparable. However, mean birthweight was significantly higher among pregnancies with GDM diagnosed by the two-step approach (3204 ± 555 versus 3009 ± 666 g;p = 0.022 ). Likewise, the rate of large-for-date tended to be higher in the two-step group, but was not significant. Conclusion . The one-step approach is associated with very high prevalence of GDM among Thai population, without clear evidence of better outcomes. Thus, this approach may not be appropriate for screening in a busy antenatal care clinic like our setting or other centers in developing countries.